The limits of political theory : Oakeshott's philosophy of civil association - McIntyre, Kenneth B. (British idealist studies. Oakeshott, 2004)
This book examines Oakeshott's political philosophy within the context of his more general conception of philosophical understanding. The book stresses the underlying continuity of his major writings on the subject and takes seriously the implications of understanding the world in terms of modality. The book suggests strongly that Oakeshott's philosophy of political activity cannot be reduced to a branch of conservatism, liberalism, or postmodernism or a theory or set of doctrines which fit ...